PENGARUH TRAINING AND DEVELOPMENT SERTA EMPOWER LEADERSHIP TERHADAP WORK PERFORMANCE YANG DIMEDIASI OLEH ORGANIZATIONAL COMMITMENT PADA CUSTOMER SERVICE PT BANK RAKYAT INDONESIA JAKARTA - Fitriyani, Fitriyani; Emilisa, Netania; Puspa, Tiara (STMIK Widuri Jakarta, 2025)
This study aims to examine the influence of training and development and empowering leadership on work performance, with organizational commitment as a mediating variable. Using a descriptive quantitative approach, the research was conducted on customer service employees at Bank BRI Jakarta through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) with the help of AMOS software. The findings show that training and development as well as empowering leadership positively influence work performance. Empowering leadership also has a positive impact on organizational commitment, which in turn positively affects work performance. However, no significant relationship was found between training and development and organizational commitment. Additionally, organizational commitment does not mediate the relationship between training and development or empowering leadership and work performance.